THE ADVANTAGES OF PROMOTING LEARNERS’ AUTONOMY IN EFL CONTEXT - Hapsari Dwi Kartika (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
This paper explains why learner autonomy is taken into account in language learning where English is a foreign language for the learners particularly in Indonesia. The definition of learner autonomy and its advantages to language learner in EFL contexts will be described within this paper. Many scholars from psychological education and English teaching and learning had proved that language learning can be improved by certain strategy. They revealed the correlation between the autonomous learning with students’ success in learning with different aspect. The definition of autonomy is similar to many different words such as self-regulated and self-determined. Finally, the writer suggests how teacher can promote the autonomous learning atmosphere in the classroom.Keywords: strategy, promoting autonomy, EFL context, Indonesia